1993
DOI: 10.1017/s0003356100006620
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of birth and weaning weight of Gudali and two-breed synthetic Wakwa beef cattle populations under selection in Cameroon: genetic and phenotypic parameters

Abstract: Genetic parameters for birth and 240-day weaning weights in Gudali and Wakwa cattle breeds in a tropical environment in Cameroon were estimated by derivative-free restricted maximum likelihood procedure using singletrait animal models with maternal effects. Performance data covered the period 1971 through 1985. Heritability estimates for direct effects of live weights at birth and weaning were 0·39 (s.e. 0·10) and 0·27 (s.e. 0·09) in Gudali cattle and 0·65 (s.e. 0·15) and 0·29 (s.e. 0·13) in Wakwa cattle, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
14
4
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
13
14
4
1
Order By: Relevance
“…At the same time, the effect of year of cows' birth on stayability to 3 yr was significant (P < 0.05). In agreement with the present study, Van der Westhuizen et al (2001) in South Africa reported the average calving success in a herd of beef cows retained to 36 mo of age varied from 1973 to 1991. There is a general lack of information on stayability patterns among Canadian herds of beef cattle.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At the same time, the effect of year of cows' birth on stayability to 3 yr was significant (P < 0.05). In agreement with the present study, Van der Westhuizen et al (2001) in South Africa reported the average calving success in a herd of beef cows retained to 36 mo of age varied from 1973 to 1991. There is a general lack of information on stayability patterns among Canadian herds of beef cattle.…”
Section: Resultssupporting
confidence: 93%
“…Again, animals born in winter and spring weighed less as yearlings than those born in the summer and fall. As expected, the influence of season in the genetic studies of the weight traits could vary according to management and climatic conditions (Assam and Nielsen 1987;Tawah et al 1993). Rege and Famula (1993) showed that the calves born in spring were the heaviest at birth and as yearlings, while those born in winter were heaviest at weaning.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In other words, selection on the base of animal's milk yield will subsequently decrease the maternal performance. Similarly, Tawah et al (1993) reported that the negative correlations between additive and maternal effects may reflect the adaptation of animals to a dry tropical environment. In addition, negative direct and maternal genetic correlations may suggest that both additive and maternal effects could be selected for breeding programs.…”
Section: Models Comparison and Rankingmentioning
confidence: 98%
“…Ainda mais discutíveis são as estimativas de correlação entre os efeitos direto e materno, publicadas para as características de crescimento, principalmente até um ano de idade, como pode ser visto nas características: peso ao nascimento e ao desmame, em que Tawah et al (1993) encontraram os valores de -0,93 e -0,68, respectivamente; peso aos 365 dias, em que Eler et al (1994) Existe o desafio de se desenvolver metodologias efetivas para comparar, e possivelmente combinar, informações de trabalhos relacionados, a fim de se realizar alguma inferência confiável sobre determinado tema. Assim, é crescente o número de estudos sobre a implementação e a melhoria de procedimentos estatísticos para a aplicação da metanálise, cujo trabalho pioneiro, no Brasil, foi efetuado por Giannotti et al (2002).…”
Section: Introductionunclassified